Treating Tropical Soils with Composted Sewage Sludge Reduces the Mineral Fertilizer Requirements in Sugarcane Production - Silva, Rafael dos Santos [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Jalal, Arshad; Alves, Rodrigo Silva [UNESP]; Elias, Nathércia Castro [UNESP]; Nascimento, Raimunda Eliane Nascimento do [UNESP]; Abreu-Junior, Cassio Hamilton; Jani, Arun Dilipkumar; Capra, Gian Franco; Nogueira, Thiago Assis Rodrigues [UNESP] (MDPI, 2024)
Conventional mineral fertilization (CMF) is a common practice in infertile sugarcane-cultivated tropical soils, increasing production costs and environmental concerns. Combining CMF with composted sewage sludge (CSS) could be a sustainable strategy. We aim to evaluate changes in soil chemical properties, macro- and micronutrient concentrations in the soil surface (Ap1; 0–25 cm) and subsurface (Ap2; 25–50 cm) horizons, after CSS application with or without CMF in sugarcane cultivation (first and second ratoon cane). Eleven treatments, featured by CSS increase rates and mixed with CMF at different concentrations, were tested in the first ratoon; during the second, the CSS residual effect was evaluated. Applying CSS in sugarcane-cultivated soils, improved the following: (i) soil organic matter, pH, the sum of bases, cation-exchange capacity, and base saturation; (ii) overall nutrient concentrations (P, K, Ca, Mg, B, Cu, and Zn). The treatments showing the best performances were those with 5.0 Mg ha−1 of CSS. Composted sewage sludge has the potential for use as an organic natural fertilizer reducing the need for CMF. When applied in infertile tropical soils, additional positive effects can be achieved, such as decreasing production costs and providing socio-economic benefits.
Keywords: by-products reuse; circular economy; energy crop; Saccharum officinarumL; soil fertility; tropical areas